History of risk assessment in toxicology - Bobst, Sol (History of toxicology and environmental health., 2017)
History of Risk Assessment in Toxicology guides the reader through the historical narrative of the evolution of risk assessment thinking in human and environmental practices. Risk assessment concepts are used in many different professional practice areas. In the health and environmental practices of risk assessment, the critical issue is often what chemical concentration in air, water, food, or a solid substance is acceptable, or considered not to result in any adverse effect. The book reviews examples from early scientific and health studies to showcase the foundations of risk assessment. The book also explores the development of risk assessment as practiced by major regulatory bodies such as the US Food and Drug Administration (FDA), the Occupational Safety & Health Administration (OSHA), and the US Environmental Protection Agency (EPA) to reveal how risk assessment has evolved in the 20th and 21st centuries. Modern technology has created opportunities in silicon in vitro, computational modeling, omics, and big data techniques to assess the toxicity of chemicals, while traditional approaches to risk assessment are being challenged with new and innovative approaches. Finally, current issues being debated and tested in risk assessment are outlined with possible future avenues suggested.